Performance of the international physical activity questionnaire (short form) in subgroups of the Hong Kong chinese population - Lee, Paul H; Yu, YY; McDowell, Ian; Leung, Gabriel M; Lam, TH; Stewart, Sunita M (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background The International Physical Activity Questionnaire (IPAQ-SF) has been validated and recommended as an efficient method to assess physical activity, but its validity has not been investigated in different population subgroups. We examined variations in IPAQ validity in the Hong Kong Chinese population by six factors: sex, age, job status, educational level, body mass index (BMI), and visceral fat level (VFL). Methods A total of 1,270 adults (aged 42.9 ± SD 14.4 years, 46.1% male) completed the Chinese version of IPAQ (IPAQ-C) and wore an accelerometer (ActiGraph) for four days afterwards. The IPAQ-C and the ActiGraph were compared in terms of estimated Metabolic Equivalent Task minutes per week (MET-min/wk), minutes spent in activity of moderate or vigorous intensity (MVPA), and agreement in the classification of physical activity. Results The overall Spearman correlation (ρ) of between the IPAQ-C and ActiGraph was low (0.11 ± 0.03; range in subgroups 0.06-0.24) and was the highest among high VFL participants (0.24 ± 0.05). Difference between self-reported and ActiGraph-derived MET-min/wk (overall 2966 ± 140) was the smallest among participants with tertiary education (1804 ± 208). When physical activity was categorized into over or under 150 min/wk, overall agreement between self-report and accelerometer was 81.3% (± 1.1%; subgroup range: 77.2%-91.4%); agreement was the highest among those who were employed full-time in physically demanding jobs (91.4% ± 2.7%). Conclusions Sex, age, job status, educational level, and obesity were found to influence the criterion validity of IPAQ-C, yet none of the subgroups showed good validity (ρ = 0.06 to 0.24). IPAQ-SF validity is questionable in our Chinese population.